2018
DOI: 10.13080/z-a.2018.105.016
|View full text |Cite
|
Sign up to set email alerts
|

Nano titanium dioxide and nitric oxide alleviate salt induced changes in seedling growth, physiological and photosynthesis attributes of barley

Abstract: Please use the following format when citing the article: Karami A., Sepehri A. 2018. Nano titanium dioxide and nitric oxide alleviate salt induced changes in seedling growth, physiological and photosynthesis attributes of barley. Zemdirbyste-Agriculture, 105 (2): 123-132

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…NO protects cells from oxidative damage by increasing the activity of antioxidant enzymes. For example, the application of a NO donor to NaCl-treated plants increased the activity of SOD, CAT, and APX [ 21 , 55 , 59 , 64 ]. Application of a NO donor to salt-treated A. corniculatum also enhanced the activity of GPX, which catalyzes the detoxification of peroxides and hydroperoxides [ 62 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…NO protects cells from oxidative damage by increasing the activity of antioxidant enzymes. For example, the application of a NO donor to NaCl-treated plants increased the activity of SOD, CAT, and APX [ 21 , 55 , 59 , 64 ]. Application of a NO donor to salt-treated A. corniculatum also enhanced the activity of GPX, which catalyzes the detoxification of peroxides and hydroperoxides [ 62 ].…”
Section: No Alleviates Salt Stress-induced Damagementioning
confidence: 99%
“…For example, wheat plants enhanced SOD, GR, APX and glutathione peroxidase (GPX) under NaCl stress (100 mM) for 30 days [99]. Barley plants had high CAT activities, SOD, APX while lower MDA content under salinity stress after application of Se-nanoparticles [75,101]. However, Habibi and Aleyasin [75] reported that excessive salts stress reduced the activity of SOD but increased the activity of malondialdehyde (MDA) in barley plants.…”
Section: Antioxidant Defense Systemmentioning
confidence: 99%
“…Moreover, TiO2 NPs in step with se may also act as nano-nutrient fertilizer to improve biomass production by invigorating plant metabolic activities (Hojjat 2019). In expansion, NPs can sequester nutrient components on their surface and serve as a nutrient stock to the plants (Karami and Sepehri 2018). TiO2 NPs may actuate oxidation-reduction reactions by the superoxide ion radical amid germination, coming about in rummaging free radicals within the sprouting seeds and oxygen produced in such preparation might moreover be expended in the respiration, which would advance enhance germination (Khot et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Nano-TiO2 uses of corrupting pesticides, plant germination, and development, crop sickness control, and so forth are appropriately viewpoint (Giorgetti et al 2019). In spite of the fact that the capability of Tio2 NPs in improving saltiness opposition has been accounted for in a few plant groups (Karami and Sepehri 2018;Lin and Xing 2007), its role in the mitigation of saltiness sway and related components is as yet obscure. The expansion of TiO2 particles in the sludge-amended soil, further modified plant development, and achieved oxidative and ultrastructural harms (Karami and Sepehri 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation